Conditionality as an Instrument of Borrower Credibility - Dhonte, Pierre (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1997)
Fund member countries that adopt market-friendly policies often encounter a credibility problem-market-friendly policies are not effective in stimulating private investment as long as there remains a significant risk of policy reversal. The root of this risk lies in the discretionary policy-making authority of governments. Committing to a program with the Fund, and endorsing its conditionality, is one instrument available to governments to overcome this difficulty. The paper develops this interpretation of conditionality and indicates some of its operational implications for Fund programs.